MANAGEMENT OF CHEMOTHERAPY-INDUCED NAUSEA AND VOMITING USING GINGER AROMATHERAPY IN CANCER PATIENTS: CASE STUDY AND LITERATURE REVIEW - Wahyu Dewi Sulistyarini; Fibrian Norma Handayani; Tarsisius Emen Astobudi (Husada Mahakam, 2022)
Background: Nausea and vomiting are prevalent symptoms of antineoplastic chemotherapy. More than 50% of patients with cancer have reported that chemotherapy-induced nausea-vomiting (CINV). One of the complementary therapies that can reduce nausea and vomiting in patients undergoing chemotherapy is ginger aromatherapy that able to change the mood, reduce psychological symptoms such as stress and also provide a comfortable feeling that can reduce nausea and vomiting in patients undergoing chemotherapy. Aim: To evaluate the effect of ginger aromatherapy in breast cancer patients undergoing chemotherapy. Methods: case study of 2 respondents with a ginger aromatherapy intervention by giving 5-10 drops of inhaler stick by inhalation for 5-10 minutes and repeated every 30 minutes for 4 times then, evaluate 12 hours later. It is also used review of research journals by Google Scholar, PubMed, Ebscho, and NCBI with the keywords. Results: After intervention before and after giving ginger aromatherapy there was a decrease in nausea and vomiting scores according to the Rhodes Index of Nausea Vomiting and Retching (RINVR). Conclusion: The use of ginger aromatherapy yielded positive results to reduce nausea and vomiting complaints in breast cancer patients undergoing chemotherapy.